Study on typical failure forms and causes of high-speed railway wheels. (November 2019) - Zhang, Guanzhen; Ren, Ruiming
Abstract: High-speed railway in china embraced rapid development in recent years. The operating environment of high-speed railway in china is unique, containing long routing of high-speed trains, low temperatures, corrosive and sand environments. As an important safety component of rolling stock, the safety and reliability of the wheels is of deep concern and high value. It is significant to carefully study and systematically summarize the damage from different failure types in high-speed railway wheels under current conditions, and determine the influencing factors and mechanisms of wheel failures in order to improve railway operation safety. In this paper, the damage forms of high-speed railway wheels in China are introduced, and the main influencing factors of wheel failure are discussed in combination with wheel damage characteristics. What's more, damage mechanism is analyzed aiming at providing theoretical references for reducing failure rate and improving train operation quality. Highlights: Main influencing factors and damage characteristics of high-speed railway wheels failure are discussed. Brittle non-metallic inclusions at a depth of 10-20 millimeters under the wheel tread are the main cause of the rim crack. Sliding spalling in wheel tread is caused by the hard and brittle martensitic phase at the shelling position. Foreign particles show greater hardness, when they pressed in, plastic deformation and micro cracks occur in wheel matrix.